A Cross-Cultural Study Of The Refusal Speech Act Among Malaysian And Moroccan Students - Mohamad, Norhayuza Muhammad; Rosli, Siti Nur Hazirah; Mamat, Anis Nabilah; Ahmad, Normah; Mohd Ramli, Zuraini; Puasa, Bashasunnahar; Wan Abdul Rahman, Ahmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Advances in technology and globalization have made it possible for multicultural societies to communicate more effectively. Understanding the characteristics of speech acts across different cultures is increasingly essential for enabling communities that speak various languages to achieve their communication goals. This study aims to identify the use of refusal speech acts among Malaysian and Moroccan students. A descriptive qualitative approach was employed, involving 34 students from Universiti Teknologi MARA, Malaysia, and the Dar El-Hadith El-Hassania Institute for Higher Islamic Studies, Morocco. The researcher used a Discourse Completion Test (DCT) containing 10 refusal scenarios adapted from Al-Issa's (1998) study. The data were analyzed deductively using the refusal strategies outlined by Beebe et al. (1990). The results indicate that Malaysian and Moroccan students predominantly use an indirect approach. The study also found that social status factors influence refusal strategies in certain situations.